2019
DOI: 10.3389/fonc.2019.00513
|View full text |Cite
|
Sign up to set email alerts
|

The Probe Based Confocal Laser Endomicroscopy (pCLE) in Locally Advanced Gastric Cancer: A Powerful Technique for Real–Time Analysis of Vasculature

Abstract: Probe based confocal laser endomicroscopy (pCLE) is an advanced technique which provides imaging of gastrointestinal mucosa at subcellular resolution and, importantly, a valid tool for the evaluation of microvasculature during endoscopic examination. In order to assess intratumoral vascularization and the efficiency of blood flow in locally advanced gastric cancer, we examined 57 patients through pCLE imaging. The vascular alterations in gastric cancer were mainly characterized by leakage and by the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Thus, controlling tumor angiogenesis is a promising therapeutic strategy for limiting tumor progression ( Weis and Cheresh, 2011 ). A wide evidence demonstrates that GC is a highly angiogenic cancer ( Chakroborty et al, 2004 ; Capuano et al, 2019 ); thus, focusing on antiangiogenesis may provide promising choices for GC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, controlling tumor angiogenesis is a promising therapeutic strategy for limiting tumor progression ( Weis and Cheresh, 2011 ). A wide evidence demonstrates that GC is a highly angiogenic cancer ( Chakroborty et al, 2004 ; Capuano et al, 2019 ); thus, focusing on antiangiogenesis may provide promising choices for GC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we were able to detect vascular changes even in non-lesion areas using pCLE, supporting the evidence that vascular changes may indicate a favorable microenvironment for carcinogenesis. We found that the mucosal vasculature of EGC patients was also characterized by vessel tortuosity, but in contrast to the regular organization observed in atrophic gastritis, these vessels often appeared patchy, as is also the case in neoplastic gastric tissue 20 . This peculiar aspect of vessel tortuosity was also found, in part, in atrophic metaplastic autoimmune gastritis.…”
Section: Discussionmentioning
confidence: 49%
“…Capillary diameter increased significantly in chronic gastritis with or without atrophy, but since the difference from normal gastric mucosa was too small, the authors felt that it was difficult to distinguish this change under real-time procedures. Recently, we thoroughly investigated the vascular features of locally advanced GC by evaluating the use of pCLE for the analysis of intratumoral angiogenesis, and we demonstrated that the functional and structural angiogenic parameters of the tumor blood network were fully detectable with this innovative endoscopic technique 20 . In this study, we provide evidence for the potential of this technique to assess vascular characteristics in gastric disease with malignant complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pCLE enables low-energy laser light to be focused and illuminated through its inner small hole to produce a tissue image, which improves the accuracy of targeted biopsy and realizes instant optical biopsy 4 . The pCLE has been used to assess the histopathology of the gastrointestinal tract in vivo 5 , 6 . The accuracy of pCLE in the diagnosis of gastrointestinal tumors has been demonstrated in previous studies 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%